Hydroxymethanesulfonate formation accelerated at the air-water interface by synergistic enthalpy-entropy effects - Jifan Li; Weiqiang Tang; Jiabao Zhu; Jinrong Yang; Xiao He (Nature Communications)
Abstract Hydroxymethanesulfonate is a key organosulfate linked to severe fine-particle pollution in fog and clouds, yet its rapid formation mechanism at the air-water interface remains elusive. Here, using metadynamics-biased ab initio molecular dynamics simulations, high-level quantum chemical calculations and reaction density functional theory, we reveal that synergistic enthalpy-entropy effects govern the nucleophilic addition between bisulfite and formaldehyde. Compared to the gaseous reaction, the aqueous reaction faces a ~5.0 kcal/mol water reorganization barrier, partly offset by polarization effects. Ab initio molecular dynamics simulations show hydrogen bonding networks facilitate proton transfer via the Grotthuss mechanism, reducing activation entropy by ~5.5 kcal/mol. At the interface, partial solvation and restricted formaldehyde motion lower the enthalpy and configurational entropy by ~1.0 and ~0.9 kcal/mol, respectively, alongside a 1.9 kcal/mol electric field effect. These combined effects enhance the interfacial reaction rate by two orders of magnitude, offering insights into heterogeneous chemistry and strategies for winter haze mitigation.